2017
DOI: 10.1080/17435390.2017.1342011
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics of iron oxide nanoparticles in the nematodeC. elegans

Abstract: Toxicogenomics of iron oxide nanoparticles in the nematode C. elegansWe present a mechanistic study of the effect of iron oxide nanoparticles (SPIONs) in C. elegans combining a genome-wide analysis with the investigation of specific molecular markers frequently linked to nanotoxicity. The effects of two different coatings were explored: citrate, an anionic stabilizer, and bovine serum albumin, as a pre-formed protein corona. The transcriptomic study identified differentially expressed genes following an exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 66 publications
0
21
0
1
Order By: Relevance
“…In fact, it is known that cytochrome P450 plays a role in the generation of oxidative stress . Furthermore, studies have shown the involvement of cytochrome P450 in the promotion of oxidative stress by NPs, including TiO 2 NPs . These findings suggest that there is possible increased oxidative stress in hESCs after TiO 2 NPs exposure.…”
Section: Resultsmentioning
confidence: 91%
“…In fact, it is known that cytochrome P450 plays a role in the generation of oxidative stress . Furthermore, studies have shown the involvement of cytochrome P450 in the promotion of oxidative stress by NPs, including TiO 2 NPs . These findings suggest that there is possible increased oxidative stress in hESCs after TiO 2 NPs exposure.…”
Section: Resultsmentioning
confidence: 91%
“…Due to sensitivity to environmental toxicants or stresses 4–6 , C . elegans has been widely used in toxicity assessment and toxicological study of various engineered nanomaterials (ENMs) 79 . Moreover, certain amount of miRNAs in response to ENMs, such as carbon-based ENMs, have been identified in nematodes 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5E illustrates that both nanoformulations are capable to decrease the amount of executioner procaspase-3. Despite both, Dox and Elli are capable to induce oxidative stress and IONs presence could plausibly lead to a deregulation of metal homeostasis,3032 no effect on the expression of MT-1/2 or MT-3 was found. Moreover, similar to free Dox, Dox@IONs-POES and Elli@IONs-PVP caused slight enhancement of p53 expression.
Figure 5( A ) Representative micrographs of wound-healing assay showing the marked effect of Dox/Elli-tethered surface-modified IONs on a migration of tested cell lines.
…”
Section: Resultsmentioning
confidence: 93%